Swiprosin‐1/EFhd2 limits germinal center responses and humoral type 2 immunity. Issue 11 (16th September 2014) - Brachs, Sebastian; Turqueti‐Neves, Adriana; Stein, Merle; Reimer, Dorothea; Brachvogel, Bent; Bösl, Michael; Winkler, Thomas; Voehringer, David; Jäck, Hans‐Martin; Mielenz, Dirk
<x xml:space="preserve">Abstract</x> Activated B cells are selected for in germinal centers by regulation of their apoptosis. The Ca2+‐binding cytoskeletal adaptor protein Swiprosin‐1/EFhd2 (EFhd2) can promote apoptosis in activated B cells. We therefore hypothesized that EFhd2 might limit humoral immunity by repressing both the germinal center reaction and the expected enhancement of immune responses in the absence of EFhd2. Here, we established EFhd2−/− mice on a C57BL/6 background, which revealed normal B‐ and T‐cell development, basal Ab levels, and T‐cell independent type 1, and T‐cell independent type 2 responses. However, T cell‐dependent immunization with sheep red blood cells and infection with the helminth Nippostrongylus brasiliensis (N.b) increased production of antibodies of multiple isotypes, as well as germinal center formation in EFhd2−/− mice. In addition, serum IgE levels and numbers of IgE+ plasma cells were strongly increased in EFhd2−/− mice, both after primary as well as after secondary N.b infection. Finally, mixed bone marrow chimeras unraveled an EFhd2‐dependent B cell‐intrinsic contribution to increased IgE plasma cell numbers in N.b‐infected mice. Hence, we established a role for EFhd2 as a negative regulator of germinal center‐dependent humoral type 2 immunity, with implications for the generation of IgE.